Technical pace bowling coaching of adolescent cricketers: A survey on practices and barriers - Bhardwaj, D.; Dwyer, D. B.; Feros, S. A. (International Journal of Sports Science & Coaching, 2025)
In cricket pace bowling, research has determined kinematic correlates to ball release speed and lumbar bone stress injury. Coaches have an important role in guiding the development of the bowling action of adolescent pace bowlers; however, it is not clear whether their knowledge and practices align with improving ball release speed and reducing lower back injury risk. This study had three aims: 1) to describe the technical coaching practices of adolescent pace bowlers, 2) to identify the barriers that coaches face in the implementation of such practices, and 3) to determine the relationship between coaches` demographic characteristics and the frequency of technical coaching. This study used a cross-sectional survey study design combined with a purposive sampling approach. Participants were cricket coaches (n = 130) in Australia aged over 18 years, who coached adolescent cricket teams (10-19 years old). Only 11.3% of coaches "occasionally" engaged in technical bowling coaching in the off-season, which increased to 37.1% during the in-season. When technical bowling coaching was undertaken, it was most common for it to last "15-30 min/session" (34.5% of coaches in the off-season and 38.2% in the in-season). The most common barrier to technical bowling coaching during the off-season was limited access to players, while barriers during the in-season were minimal and varied. Younger coaches and older players were associated with more frequent technical coaching in the off-season. Future coaching educational programmes could help coaches to work around the player-access barrier by encouraging them to prescribe training drills in the off-season.